Team performance and satisfaction: a link to cognitive style within a process framework - Basadur, Min; Head, Milena M.; McMaster University, Michael G. DeGroote School of Business, Management of Innovation and New Technology Research Centre (My University, 2001)
Effective teamwork is becoming increasingly important to organizational success. Advances in network and communication technology have allowed companies to widen their potential team member base, however we still need to better understand how to structure top-performing teams. This paper proposes forming teams based on their cognitive style, rather than personality, within a process framework.
An experiment was conducted to investigate the innovative performance of problem solving groups with three different blends of cognitive styles. As predicted, groups with a heterogeneous blend of styles outperformed groups with completely or partially homogeneous blends. On the other hand, team members' satisfaction scores were lower for heterogeneous teams than either the completely or partially homogeneous teams. There was preliminary evidence that among groups with heterogeneous blends, those with smaller style dispersions might be expected to outperform those with larger style dispersions. There was also room for some speculation that a curvilinear relationship might exist for team members' satisfaction as a function of diversity in team member cognitive style. Implications of these findings are discussed.
29, [10] leaves : ; Includes bibliographical references (leaves 26-29) ; "March 2001".
Keywords: Teams in the workplace Group problem solving